2005
DOI: 10.1139/x05-226
|View full text |Cite
|
Sign up to set email alerts
|

Exponential fertilization of Pinus monticola seedlings: nutrient uptake efficiency, leaching fractions, and early outplanting performance

Abstract: Abstract:We evaluated nutrient uptake efficiency and subsequent leaching fractions for western white pine (Pinus monticola Dougl. ex D. Don) seedlings grown with exponentially increasing or conventional (constant) fertilization in a greenhouse. Conventional fertilization was associated with higher leachate electrical conductivity and greater nutrient losses, which were more pronounced for the more mobile NO 3 -N than for NH 4 -N. Exponential fertilization increased seedling nitrogen (N) uptake efficiency (75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 24 publications
4
54
2
4
Order By: Relevance
“…When seedlings applied with the same dose of N were compared, higher nutrient uptake efficiency was seen in seedlings conventionally fertilized at the last harvest, although exponentially fertilized seedlings had greater nutrient uptake efficiency than the conventionally fertilized seedlings at the former three measurement times. This was inconsistent with the study of Dumroese et al (2005) on Pinus monticola Dougl. ex D. Don in which exponential fertilization increased seedling N uptake efficiency by 75%, although exponentially fertilized seedlings received 45% less fertilizer than conventionally fertilized seedlings during the experiment.…”
Section: Nutrient Uptake Dynamicscontrasting
confidence: 86%
See 1 more Smart Citation
“…When seedlings applied with the same dose of N were compared, higher nutrient uptake efficiency was seen in seedlings conventionally fertilized at the last harvest, although exponentially fertilized seedlings had greater nutrient uptake efficiency than the conventionally fertilized seedlings at the former three measurement times. This was inconsistent with the study of Dumroese et al (2005) on Pinus monticola Dougl. ex D. Don in which exponential fertilization increased seedling N uptake efficiency by 75%, although exponentially fertilized seedlings received 45% less fertilizer than conventionally fertilized seedlings during the experiment.…”
Section: Nutrient Uptake Dynamicscontrasting
confidence: 86%
“…Traditionally, nutrients were applied in a single or constant rate of fertilization, which might result in early toxicity due to over-fertilization and later nutrient deficiency in the growing season (Xu and Timmer 1998), and nutrient uptake efficiency could be reduced since applied nutrients were not taken up immediately by seedlings and might be lost by leaching (Dumroese et al 2005). Therefore, supplying full-element solutions to plants in lower nutrient concentration but higher nutrient addition rate during the exponential growth phase may generally provide a better rationale to build steady-state nutrition in seedlings, which subsequently induces maximum plant growth (Ingestad and Lund 1986;Ingestad 1987;Timmer and Armstrong 1987;Zabek and Prescott 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To further augment height growth in red pine seedlings, we suggest two possible options: (i) application of fertilizer earlier in fall to take advantage of warmer soil temperatures and atmospheric conditions that are conducive to seedling growth; and, (ii) modifying the current summer fertilizer pattern to an exponential application regime, which should increase nutrient uptake efficiency (Dumroese et al, 2005) and thereby minimize leaching losses in sandy soils with low nutrient retention. These factors could further promote height growth as Birge et al (2006) observed that exponentially fertilized northern red oak (Quercus rubra) and white oak (Q. alba) under bareroot cultivation were 99-162% and 5-66% taller, respectively, than unfertilized seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is global interest in optimizing fertilizer application in the nursery for effective nutrient storage by seedlings (Dumroese et al 2005;Salifu et al 2009;Li et al 2014). …”
Section: Introductionmentioning
confidence: 99%